Kesesuaian Pertimbangan Hakim Terhadap Kriteria Plagiarisme Undang – Undang No 28 Tahun 2014 (Analisis Putusan Nomor 31/ PDT.SUS-HAK CIPTA /2020/ PN.JKT.PST) - Reza Fauzia Hanum; Yudho Taruno Muryanto (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the criteria for plagiarism of fine arts according to Law Number 28 of 2014 concerning Copyright. In addition, it also seeks to determine the basis for the judge's consideration in Decision Number 31 / Pdt.Sus-Copyright / 2020 / Pn.Jkt.Pst. In this study, normative legal research was prescriptive. Normative is prescriptive, namely, examining library materials indicated in written regulations. The approaches used in writing this law are the case and statutory approaches. The results of this research, according to Law Number 28 of 2014 concerning Copyright, the criteria for plagiarism of works of fine art are if they meet the elements of 1) the existence of similarities in whole or in part that are substantial, 2) the recognition of private property to imitation works and 3) cause losses to the creator of imitation of works. In the judge's consideration in deciding the alleged case of plagiarism, the judge should take into account the following: 1) Proving the similarity between Love Light and Urban Light; 2) There is a loss incurred by the Plaintiff. In this case, the judge's consideration is based on the regulations of Law Number 28 of 2014 concerning copyright, and the plaintiff can also prove all of them so that the defendant is found guilty.